OPHTHALMIC IN-SITU SUSTAINED GEL OF CIPROFLOXACIN, PREPARATION AND EVALUATION STUDY - Al-bazzaz, Fadia Yassir; Al-kotaji, Myasar (International Journal of Applied Pharmaceutics, 2018)
Objective: This work aims to formulate and evaluate an ophthalmic in-situ gel of ciprofloxacin hydrochloride (HCl) using poloxamer 407 (P407) as a gelling agent and hydroxypropyl methylcellulose (HPMC) as a viscosity modifier. The objective of this work was to prolong the contact time as the in-situ gel will be converted into a gel upon contact with the cul-de-sac. Methods: Ciprofloxacin HCl ophthalmic in-situ gel was prepared by utilizing (P407) as a temperature-dependent polymer while hydroxypropyl methylcellulose was used as a viscosity modifier. The system was evaluated for physical appearance, pH, drug content, sterility, irritancy and stability. In addition, gelation temperature and a viscosity at different shear rates and different temperatures were studied. The compatibility of the polymer with ciprofloxacin was studied by using fourier transform infrared spectroscopy (FTIR). The in vitro release of the drug was also evaluated and supported by a preliminary in vivo test. Results: The results showed that the prepared formulas were clear, with acceptable pH and the drug contents were within the acceptable limits. FTIR results detected no incompatibility between poloxamer 407 and ciprofloxacin HCl. Notably, the viscosity of the system showed a pseudoplastic behaviour where a reduction in viscosity upon increasing the shear rate was observed. The in vitro release study confirmed the prolongation of the release of the optimized formula (F6) up to 8 h. Upon application of F6 into eyes of rabbits there was no irritancy. In addition, in vivo elimination study showed a prolonged contact for the in-situ gel in comparison with the rapid clearance of eye drop. Stability study indicated the stability of the optimized formula (F6). Conclusion: The prepared optimized formula (F6) represents a successful, safe, stable and prolonged release in-situ gel formula of ciprofloxacin.